Ecophysiological traits change little along a successional gradient in a tropical dry deciduous woodland from Margarita Island, Venezuela - Ávila-Lovera, Eleinis; Urich, Rosa; Coronel, Ilsa; Tezara, Wilmer (Frontiers in Forests and Global Change, 2023)
Tropical dry forests (TDFs) are the most threatened terrestrial ecosystems and studying how functional traits of plant species change as secondary succession advances is important for understanding how and how fast can TDFs recover from disturbance. In this work we asked the question: how do functional traits change during secondary succession in a tropical dry woodland? We studied functional traits, especially ecophysiological traits, such as gas exchange, plant-water relations, leaf carbon isotope composition (δ13C), specific leaf area (SLA) and nitrogen concentration, in shrubs and trees in three successional stages (6 and 20 years after abandonment, and the dry deciduous woodland, 6 years, 20 years, and DW, respectively) along a successional gradient in a TDF in both wet and dry seasons to understand how TDFs recover after disturbance by opencast sand mining. During the wet season, similar mass-based photosynthetic rates (Amass), water potential, relative water content, instantaneous and intrinsic water-use efficiency (WUE and IWUE) and SLA were found in the 6 years and DW stages. During seasonal drought, similar reductions in these variables were observed for all three successional stages. However, δ13C of the 6 years species was higher than in 20 years and DW species, indicating a higher long-term integrated WUE in the former due to a strong reduction in stomatal conductance (gs) in the dry season. Species from the DW seem to couple metabolic changes to their characteristically low gs, such that nitrogen concentration per unit mass explained 86% of the variation in Amass. Given the functional similarity among species from the different successional stages, native species from the DW stage could have good physiological performance in the 6 and 20 years sites, and therefore could be used to restore these degraded areas.